Porcine oocyte mtDNA copy number is high or low depending on the donor. Issue 4 (18th December 2015) - Pedersen, Hanne Skovsgaard; Løvendahl, Peter; Larsen, Knud; Madsen, Lone Bruhn; Callesen, Henrik
Summary: Oocyte capacity is relevant in understanding decreasing female fertility and in the use of assisted reproductive technologies in human and farm animals. Mitochondria are important to the development of a functionally good oocyte and the oocyte mtDNA copy number has been introduced as a useful parameter for prediction of oocyte competence. The aim of this study was to investigate: (i) if the oocyte donor has an influence on its oocyte's mtDNA copy number; and (ii) the relation between oocyte size and mtDNA copy number using pre- and postpubertal pig oocytes. Cumulus–oocyte complexes were collected from individual donor pigs. The oocytes were allocated into different size-groups, snap-frozen and single-oocyte mtDNA copy number was estimated by quantitative real-time PCR using the genes ND1 and COX1. Results showed that mean mtDNA copy number in oocytes from any individual donor could be categorized as either 'high' (≥100, 000) or 'low' (<100, 000) with no difference in threshold between pre- and postpubertal oocytes. No linear correlation was detected between oocyte size and mtDNA copy number within pre- and postpubertal oocytes. This study demonstrates the importance of the oocyte donor in relation to oocyte mtDNA copy number, irrespectively of the donor's puberty status and the oocyte's growth stage. Observations from this study facilitate both further investigations of the importance of mtDNA copy number and the unravelling of relations between different mitochondrial parameters and oocyte competence.